E-Extension / E-Agriculture and Role of Library and Information Centers - Manoj Kumar (Journal of Agricultural Extension Management, 2021)
Information has always been an essential element in all the time in our society. We need information to decide and do the right thing at the right time. Information technology does not have only changed our lifestyle but also the way of dealing with agriculture. As information is affecting agriculture like other sectors, the role of libraries and information centers has increased. Information has become a key instrument to improve and change the course of action. Traditionally, the agriculture sector was full of uncertainty, but with the help of information, we can drastically change the result and impact in modern times. This paper outlined some significant points to describe the role of libraries and information centers and the current developments of technologies, in the context of e-extension or eagriculture and their impact on the farmers.